Peningkatan Akuntabilitas Desa Melalui Pendampingan Penyusunan Laporan Keuangan di Desa Tamarenja - Muhammad Din; Muhammad Ilham Pakawaru; Faizal Azdar; Andi Ainil Mufidah Tanra; Rudy Usman; Andi Mappanyukki; Daud Ruranto Buntulabi (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2024)
Financial reports are presented by both business organizations (private) with the aim of seeking profit and public organizations (non-profit) whose main goal is not profit but to serve the community. The government is a public organization that presents its financial reports as a form of accountability to the public, especially those related to financial management. The government has provided village fund assistance to all villages in Indonesia since 2015. Village funds provided by the government aim to make villages more productive and improve the welfare of village communities. The increase in the productivity of this village can be seen from its increased economic development, the number of people working and owning businesses has increased, and the quality of life has improved. One of the sources of village revenue is the central and regional financial balance funds received by the district/city which in its distribution for each village is distributed proportionally, namely at least 10% which is called the village fund allocation. In addition, the allocation of village funds will be used as a support for village autonomy activities so that they can be maximized in providing services, development, and community empowerment at the village level.